Reproxalap in patients with seasonal allergic conjunctivitis: a systematic review and meta-analysis - Ammar Elgadi; Malaz M. Abdalmotalib; Tibyan Noorallah; Egbal Abdelazim; Fatma Ali Merghani Mohammed (Journal of Ophthalmic Inflammation and Infection)
Abstract Introduction Seasonal allergic conjunctivitis (SAC) is a hypersensitivity condition characterized by itching, tearing, and redness. It affects over 20% of the general population with limited therapeutic options. Reproxalap, a novel small-molecule aldehyde trap, has emerged as a potential treatment option for SAC by targeting reactive aldehydes involved in inflammation. In this systematic review and meta-analysis, we assessed the efficacy and safety of Reproxalap in treating SAC. Methods Multiple databases were searched including PubMed, Cochrane Library, Scopus, and Google Scholar, to identify relevant studies. Clinical trials involving patients diagnosed with SAC and treated with Reproxalap (0.25% or 0.5%) were included. The primary outcomes were symptom relief (efficacy) and side effects (safety). Data extraction and risk of bias assessment were performed independently by two reviewers. Meta-analysis was conducted using RevMan 5.4 software. Results Five RCTs involving 625 participants were included. Reproxalap significantly reduced ocular itching compared to control groups for both 0.25% (SMD: -0.31, 95% CI: -0.50 to -0.13, P = .001) and 0.5% concentrations (SMD: -0.31, 95% CI: -0.51 to -0.10, P = 0.004). No significant difference was observed between the two doses (SMD: -0.02, 95% CI: -0.23 to 0.19, P = 0.83). Side effects were more frequent in both Reproxalap groups compared to controls, with odds ratios of 35.31 (95% CI: 17.83 to 69.90, P < 0.00001) for 0.25% and 45.64 (95% CI: 18.49 to 112.66, P < 0.00001) for 0.5%. The 0.5% dose had significantly higher odds of side effects compared to the 0.25% dose (OR: 1.66, 95% CI: 1.10 to 2.51, P = 0.02). Heterogeneity was low for all outcomes (I2 = 0%). Conclusion Reproxalap reduces ocular itching associated with SAC. While both 0.25% and 0.5% concentrations are effective, safe and tolerable. Further research should focus on the long-term benefits and applicability of Reproxalap on diverse populations.